Large anomalous Nernst effect in thin films of the Weyl semimetal Co2MnGa - Reichlova, Helena; Schlitz, Richard; Beckert, Sebastian; Swekis, Peter; Markou, Anastasios; Chen, Yi-Cheng; Kriegner, Dominik; Fabretti, Savio; Park, Gyu Hyeon; Niemann, Anna; Sudheendra, Shashank; Thomas, Andy; et al. (Applied Physics Letters, 2018)
The magneto-thermoelectric properties of Heusler compound thin films are very diverse. Here, we discuss the anomalous Nernst response of Co2MnGa thin films. We systematically study the anomalous Nernst coefficient as a function of temperature, and we show that unlike the anomalous Hall effect, the anomalous Nernst effect in Co2MnGa strongly varies with temperature. We exploit the on-chip thermometry technique to quantify the thermal gradient, which enables us to directly evaluate the anomalous Nernst coefficient. We compare these results to a reference CoFeB thin film. We show that the 50-nm-thick Co2MnGa films exhibit a large anomalous Nernst effect of -2 μV/K at 300 K, whereas the 10-nm-thick Co2MnGa film exhibits a significantly smaller anomalous Nernst coefficient despite having similar volume magnetizations. These findings suggest that the microscopic origin of the anomalous Nernst effect in Co2MnGa is complex and may contain contributions from skew-scattering, side-jump, or intrinsic Berry phase. In any case, the observed anomalous Nernst coefficient of -2 μV/K at 300 K is large compared to the values measured in other thin films and makes this material system a very promising candidate for efficient spin-caloritronic devices.
CRIS-Team Scopus Importer:2022-04-14